Exploring the UNIX system (Hayden Bk. Co., 1984)
This work introduces the computer novice to the UNIX operating system, describing how operating systems work, how the UNIX file system is organized and how to create, copy, rename and remove files and more. The material is relevant to release 3 of UNIX.